Standar Mutu Pengabdian pada Masyarakat dan Profesionalisme Dosen - Ni Made Anggreni (UHN IGB Sugriwa Denpasar, 2015)
Higher education institutions should adapt the development of science and technology in order to meet the society demand along the ages. They are expected to produce human resources with academic and leadership capability and ethics who are also adaptive to the technological development. In order to achieve that, the instituations are required to carry out quality research and social service programs that can improve the societies. The programs should be based on science and the implementation of the education and research with clear targets. However, in practice, the social service programs are often irrelevant to the society needs as well as to the fields of the lecturers and students involved in the programs. This proves the gap between the ideal and the real condition of the Indonesian higher education quality. The situation is influenced by several factors, including the poor management, economics, and social realities. In order to overcome them, a comprehensive program for developing the profesionalism of the lecturers is needed in which the government, the instituation, and the society are all involved. The Minister of Education and Culture Affair Regulation No 49/2014 regulates the standard for the social service, which is an important part of the Tri Dharma Perguruan Tinggi. According to it, the program should be organized by the Social Service Board with its principles for institutionalism, education, cooperation, sustainability, social empowerment, and regional development.